622 Congenital Cystic Adenomatoid Malformation: is it Always Bad News?. (October 2012) - Yadav, K; Vasudev, D; Budd, J; Akuma, A O
Abstract : Aim: To evaluate whether conservative approach to management of asymptomatic neonates with antenatal diagnosis of congenital cystic adenomatoid malformation of the lungs (CCAM) is safe and appropriate. Method: We undertook a retrospective review of all cases with antenatal diagnosis of CCAM from 2004–2010 in a lead perinatal centre. Pertinent data was extracted and the outcome and management of all affected infants were reviewed up to 1year of age. Results: Twenty-six pregnancies were complicated with CCAM. Three pregnancies were excluded: two terminated and one fetus had bronchogenic cyst. Twenty-three singleton pregnancies were included in the study. There was a threefold increase in CCAM in the last two years of the study as compared to the first two years. CCAM lesions underwent complete resolution in four (17%) fetuses, partial resolution in 12 (52%), remained static in four (17 %) and increased in one (4%) fetus. Eleven (48%) fetuses did not have any associated complications. 15 (65%) infants were asymptomatic at birth and eight (35%) were symptomatic. In two symptomatic infants respiratory distress resolved spontaneously. Three symptomatic infants had surgery and one died. A further three symptomatic preterm infants died due to extreme prematurity. All the surviving, non-operated infants: 17 (74%) were followed up and none required hospitalization or surgical interventions in infancy. Conclusions: Our study shows that conservative management of asymptomatic infants with CCAM; consisting of symptoms surveillance, radiological investigations and consideration for surgery if symptoms arise and persist is safe and may be more appropriate to elective surgery in infancy.